2018
DOI: 10.3390/atmos9080298
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Sources of Marine Aerosol over the Western North Pacific Ocean in Winter

Abstract: Atmospheric deposition of long-range transported continental substances from natural and anthropogenic sources affects biogeochemical processes in marine systems. Emissions of sea spray contribute aerosol particles to the marine atmosphere. Despite the importance of continental dispersion and atmospheric processes involving aerosol particles within remote marine atmosphere, knowledge of the sources of various water-soluble ions is limited because of insufficient observations. Concentrations of Total suspended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…105–107 Nitrate are often internally mixed with chloride ions in the atmosphere through the chloride depletion reactions of sea spray particles. According to field measurements, the molar ratio of halides to nitrate in fresh sea spray aerosol is usually higher than 1.0, 108–112 whereas that in urban aerosol or aged marine aerosol falls in the range of 0–1.1. 113–117 Wingen et al reported that the coexistence of chloride ions results in an enhanced gaseous NO 2 production from deliquesced nitrate aerosol particles under illumination by a factor of 1.6 to 2.4.…”
Section: Factors Affecting Particulate Nitrate Photolysismentioning
confidence: 99%
“…105–107 Nitrate are often internally mixed with chloride ions in the atmosphere through the chloride depletion reactions of sea spray particles. According to field measurements, the molar ratio of halides to nitrate in fresh sea spray aerosol is usually higher than 1.0, 108–112 whereas that in urban aerosol or aged marine aerosol falls in the range of 0–1.1. 113–117 Wingen et al reported that the coexistence of chloride ions results in an enhanced gaseous NO 2 production from deliquesced nitrate aerosol particles under illumination by a factor of 1.6 to 2.4.…”
Section: Factors Affecting Particulate Nitrate Photolysismentioning
confidence: 99%
“…47−53 We found that at [Cl − ]/[NO 3 − ] > 1.0, the halide-enhanced nitrate photolysis had little influence on the sulfate production due to the reduced nitrate concentration, and thus may not be important in fresh marine/coastal aerosols. The low concentration levels of nitrate in fresh marine aerosol (1−2 μg/m 3 ) 47,48,51 may also make the halideenhanced nitrate photolysis less relevant than in inland or urban aerosol. 43,44,46 On the other hand, aged sea-salt aerosols due to the chloride depletion reactions can result in lower [Cl − ]/[NO 3 − ] ratios, increasing the enhancement effect.…”
Section: ■ Atmospheric Implicationmentioning
confidence: 99%
“…Our analysis also shows that Clin coarse and fine fractions are highly correlated with Mg 2+ (0.97 in wet season and 0.96 in dry season) combining all sites, except at ADF for which these correlation coefficients decrease to 0.68 and 0.95 in the wet and dry season, respectively. As Cl -, Na + and Mg 2+ are associated with sea salt origin or secondary aerosol production (Xiao et al, 2018), these results indicate that coarse Cl -, Na + and Mg 2+ particles (>1μm) from this study have the same "sea salt" origin at AT, CT, and CT, which is different at the ADF site. Their abundance in the wet season could be related to the influence of the predominant wind direction mainly oriented towards the North-East ( Figure 5) which transports marine aerosols to these sites.…”
Section: Water-soluble Ionic Speciesmentioning
confidence: 59%